Characterization of a Novel Transferrin Receptor in Bovine Strains of Pasteurella multocida - Ogunnariwo, Julius A. (American Society for Microbiology, 2001)
Analysis of bovine respiratory isolates of Pasteurella multocida demonstrated that six of nine strains tested were capable of growth dependent upon bovine transferrin and of specifically binding ruminant transferrins. A single 82-kDa protein was affinity isolated from the P. multocida strains with immobilized bovine transferrin. In contrast to what has been observed in other species, binding of this protein to immobilized transferrin was specifically blocked by the N-lobe subfragment of bovine transferrin. A single gene encoding the 82-kDa protein was flanked by a leucyl-tRNA synthetase gene and an IS1060 element, in contrast to other species where genes encoding the two receptor proteins (TbpB and TbpA) are found in an operonic arrangement. A similar gene arrangement was observed in all of the receptor-positive strains, in spite of the observation that they belonged to different genomic groups. Analysis of the deduced amino acid sequence of the receptor protein indicated that it is a member of the TonB-dependent outer membrane receptor family, and although it is related to transferrin and lactoferrin receptor proteins (TbpAs and LbpAs) from other species, it differs substantially from other members of this group. Amino acid alignments suggest that the reduced size (20 kDa smaller) of the P. multocida TbpA is primarily due to the absence of larger predicted external loops. Collectively these results suggest that P. multocida has a single, novel receptor protein (TbpA) that is capable of efficiently mediating iron acquisition from bovine transferrin without the involvement of a second receptor protein (TbpB).